DEVELOPMENT OF A MAYONNAISE WITH CHITOSAN AS NATURAL ANTIOXIDANT - Garcia, Mario; Silva, Yanisleidi; Casariego, Alicia (Emirates Journal of Food and Agriculture, 2014)
The aim of this work was to evaluate the influence of addition of chitosan as a natural antioxidant in the stability of mayonnaise. Three formulations were developed with EDTA and chitosans with different molecular weight. Mayonnaises were stored at 37; 47 and 57ºC for 63 days. During this period, it was analyzed weekly for the peroxide and acidity index. The mayonnaises with chitosan obtained better results for the attributes of typical odor and taste respect to the mayonnaise control. It has been observed that addition of chitosan slowed down the lipid oxidation process of mayonnaises during 63 days of accelerated storage. The mayonnaise with chitosan with the bigger molecular weight showed better stability during accelerated storage at all temperatures. Further research on the effect of the deacetylation degree of chitosan in the preservation of mayonnaise is recommended to assess the efficacy of chitosan as a natural preservative for food.